Interdisciplinarity between the normative and the a esthetic in the rhetorical Lesson Towards a textual linguistic approach - Hassane, Hammani (Journal of Humanities & Social Sciences, 2020)
It is noteworthy that the grammatical text lesson is a complex process because it requires from researchers the use of mechanisms that are difficult to verify in reality. This is due to the fact that its source is still in the mothers of books while others are written in foreign languages which need to be translated. Therefore, the provision of the linguistic, the grammatical and the rhetorical for this lesson necessitates referring to the Arab heritage, through the books of the miracles of the Koran, and books of interpretation and rhetoric’s because they constitute the secret of the semantic, grammatical and rhetorical industry, on the basis that these levels are inseparable in the textual analysis. We came to the following conclusions: - Emphasis on the relationship between the science of meanings and the science of grammar since researchers cannot separate them. - There are some Arab scientists who are aware of the relationship between language, grammar and meaning which has been included in their scientific writings. - The rhetorical and the linguistic texts differ in a quality given the type of impact they have on the recipient. - Both are based on the study of the logical mental relationship between the sentences of the text. - The grammar of the text and rhetoric’s strive towards finding justifications from within the text.